Studies on an L-leucine hydriodide semiorganic crystal for frequency conversion applications. (18th March 2016) - Baskaran, P; Vimalan, M; Anandan, P; Bakiyaraj, G; Kirubavathi, K; Praveen, S G; Selvaraju, K
Abstract: An L-leucine hydriodide semiorganic crystal has been synthesized and grown by a slow evaporation technique. The lattice parameters of the grown crystal have been confirmed using single-crystal x-ray diffractometry. Various functional groups present in the crystal were identified by Fourier transform infrared (FTIR spectral) assessment. The optical transmission percentage of the crystal was ascertained by UV–vis-near-infrared (NIR) studies. The thermal stability of the crystal was determined by thermogravimetric and differential thermal analysis curves. The mechanical behavior of the crystal was studied using the Vicker's microhardness analysis. The dielectric properties of the crystal have been investigated for varying temperatures. The second-harmonic generation efficiency was measured by the Kurtz and Perry powder technique and the efficiency is comparable to that of potassium dihydrogen orthophosphate.